SahabatInklusi: A catalyst for change toward a more inclusive and disability-friendly Indonesia through artificial intelligence (AI) and computer vision - Mahanani, Aniza Helwa; Zahara, Niquita Aislam Az; Ramadhani, Nayla Masyitha (Journal of Gender Equality Disability Social Inclusion and Children, 2026)
Background: People with disabilities represent one of the world's largest marginalized groups. In Indonesia, despite progressive legislation, significant implementation gaps persist in accessibility. Current technological solutions are often fragmented, failing to provide comprehensive support for diverse user needs. Methods: This research adopts a conceptual design-based approach, combining a systematic literature review, policy analysis, and system design thinking. The methodological framework integrates the Pentahelix multi-stakeholder collaboration model with Community-based development (CBD) principles. A SWOT analysis was conducted to evaluate the platform's strategic positioning and implementation feasibility. Findings: The conceptual framework for "SahabatInklusi" incorporates four synergistic features: real-time sign language translation using Computer Vision and deep learning, AI-powered navigation assistance with voice commands, interactive mapping of accessible public facilities, and an integrated emergency response system. The SWOT analysis reveals significant strengths in technological integration and a multi-disability approach, while identifying critical dependencies on digital infrastructure and data security. Conclusion: SahabatInklusi represents a paradigm shift in assistive technology design, positioning digital innovation as a catalyst for social inclusion rather than merely a technical solution. The platform demonstrates how integrated AI can transform accessibility into a central component of the digital ecosystem, thereby contributing to achieving Sustainable Development Goal 9 (Industry, Innovation, and Infrastructure) in Indonesia. Novelty/Originality of this article: The research introduces a novel integration of AI and Computer Vision within an inclusive design framework that incorporates multi- stakeholder collaboration models. This holistic approach addresses both the technological and social dimensions of accessibility, offering a replicable framework for developing comprehensive disability-inclusive solutions in emerging markets.